ECOPEDAGOGY-BASED SCIENCE LEARNING ENHANCES ENVIROMENTAL AWARNESS IN INDONESIA ELEMENTARY STUDENTS: SLR 2021-2025 - Nurul Rahmawati; Intan Sari Rufiana; Aynin Mashfufah; Mardhatillah Mardhatillah; Slamet Arifin (Universitas Bhinneka PGRI, 2026)
This study aims to examine science education based on eco-pedagogy as an alternative approach to increasing environmental awareness among elementary school students. The method used is a Systematic Literature Review (SLR) with the stages of identification, screening, eligibility, and inclusion based on the PRISMA protocol. The data sources are accredited SINTA national scientific articles published between 2021 and 2025. Of the 222 articles identified, 5 articles met the inclusion criteria and were further analyzed. The results showed that eco-pedagogy-based science learning was effective in increasing students' environmental awareness, love of nature, and ecological literacy. Its implementation was carried out through various strategies, such as project-based learning, the Jelajah Alam Sekitar (JAS) model, and interactive media such as the NARJI board game and the ecobrick project. In addition, the role of teachers as facilitators of critical reflection is key to success in fostering ecological awareness. This study confirms that ecopedagogy is capable of harmoniously integrating cognitive, affective, and psychomotor dimensions and contributes to the achievement of the Sustainable Development Goals (SDGs), especially goals 4 and 13.